Datos de investigación del artículo Sutural complexity and body size in Cretaceous ammonoids: Macroevolutionary decoupling of correlated features - Pérez-Claros, Juan Antonio (Elsevier, 2021)
Fractal dimension (Df) and whorl perimeter (Wp) in millimeters for the ammonoid genera studied are supplied as an excel file
Supplementary data. Fractal dimension (Df) and whorl perimeter (Wp) in millimeters for the ammonoid genera studied are supplied as an excel file
Keywords: Cefalópodos; Tamaño corporal; Macroevolución; Cretaceous ammonoids; Body size; Fractal dimension; Septal complexity; Macroevolution